2015
DOI: 10.1038/srep13480
|View full text |Cite
|
Sign up to set email alerts
|

Bottom-up Fabrication of Graphene on Silicon/Silica Substrate via a Facile Soft-hard Template Approach

Abstract: In this work, a novel soft-hard template method towards the direct fabrication of graphene films on silicon/silica substrate is developed via a tri-constituent self-assembly route. Using cetyl trimethyl ammonium bromide (CTAB) as a soft template, silica (SiO2) from tetramethoxysilane as a hard template, and pyrene as a carbon source, the self-assembly process allows the formation of a sandwich-like SiO2/CTAB/pyrene composite, which can be further converted to high quantity graphene films with a thickness of ~1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

6
2

Authors

Journals

citations
Cited by 103 publications
(65 citation statements)
references
References 37 publications
2
58
0
Order By: Relevance
“…Figure 1b shows a scanning electron microscope image of a 2D layered GO film on a silica substrate, with up to five layers of GO. Our GO coating approach, unlike the sophisticated transfer processes employed for coating other 2D materials such as graphene, [ 47,48 ] enables large‐area, transfer‐free, and high‐quality GO film coating on integrated photonic devices, with highly scalable fabrication processes and precise control of the number of GO layers (i.e., GO film thickness).…”
Section: Device Fabrication and Characterizationmentioning
confidence: 99%
“…Figure 1b shows a scanning electron microscope image of a 2D layered GO film on a silica substrate, with up to five layers of GO. Our GO coating approach, unlike the sophisticated transfer processes employed for coating other 2D materials such as graphene, [ 47,48 ] enables large‐area, transfer‐free, and high‐quality GO film coating on integrated photonic devices, with highly scalable fabrication processes and precise control of the number of GO layers (i.e., GO film thickness).…”
Section: Device Fabrication and Characterizationmentioning
confidence: 99%
“…However, none of these demonstrations were based on CMOS compatible platforms. Generally, the integration of 2D materials on CMOS compatible platforms requires layer transfer processes, where exfoliated or chemical vapor deposition grown 2D membranes are attached onto dielectric substrates (e.g., silicon and silica wafers). Despite its widespread implementation, the transfer approach itself is complex, which makes it difficult to achieve precise patterning, as well as flexible placement and large‐area continuous coating on integrated devices.…”
Section: Introductionmentioning
confidence: 99%
“…Graphene has been proved to be an excellent nonlinear optical material [12,13]. In our previous study, we demonstrated a large Kerr coefficient of graphene (n 2 ∼10 −12 m 2 · W −1 ), which is 6 orders of magnitude larger than that of silicon [14]. Combining graphene with silicon photonic devices offers a possible solution towards high-efficiency and broadband FWM [15,16].…”
Section: Introductionmentioning
confidence: 93%
“…The integrals are performed in the core and cladding materials with either the propagating or the evanescent electric field. The nonlinear Kerr coefficients of the silicon, the silica, and the graphene are set to be 4.5 × 10 −18 , 3 × 10 −20 , and 1 × 10 −12 m 2 · W −1 , respectively [14,24,25]. Based on Eq.…”
Section: Device Design and Operation Principlementioning
confidence: 99%